(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: Adolescents are a vulnerable group and subject to countless experiences of violence, which can cause negative impacts on their life and development. Objectives: To verify the frequency of psychological violence and neglect against adolescents in Espirito Santo, from 2011 to 2018, and characterize the victims, the aggressor and the events. Methods: Epidemiological, descriptive study carried out with reported data on violence against adolescents between 10 and 19 years old, registered in the Information System for Diseases and Notification (SINAN), between 2011 and 2018 in Espírito Santo. Data analysis was performed using descriptive statistics (crude and relative frequency) with 95% confidence intervals. Bivariate analyzes were performed using Pearson’s Chi-Square test. Results: 386 reported cases of psychological violence (N= 144; P= 1.6%) and neglect (N= 242; P= 2.8%) were analyzed. A higher frequency of psychological violence occurred in the victim’s home, repeatedly, by a single adult male aggressor (p < 0.05). Neglect was more prevalent in boys, adolescents with some disability/disorder and between 10 and 14 years old, and more frequently perpetrated by someone in the family and female (p<0.05). Conclusion: The data collected point to the invisibility of violence within the family and its marked gender character. The qualification of professionals who offer assistance is a basic point of transformation in the naturalization of violence.